Opinions of Health Professionals on Tailoring Reproductive Health Services to the Needs of Adolescents - Boamah-Kaali, Ellen Abrafi; Kaali, Seyram; Manu, Grace; Gyaase, Stephaney; Adeniji, Elisha; Owusu-Agyei, Seth; Asante, Kwaku Poku (International Journal of Reproductive Medicine, 2018)
Introduction. Tailoring sexual and reproductive health programs and services to the needs of adolescents will help adolescents make informed decisions and choices regarding their sexual and reproductive health. Objective. To assess the opinions of service providers on tailoring sexual and reproductive health services to the needs of adolescents. Method. A qualitative study using indepth interviews was held among eight decision-makers and service providers in two hospitals within the Kintampo North Municipality and Kintampo South District as well as the Municipal and District Health Directorates in Kintampo North and South between April and May 2011. Results. All respondents expressed the opinion that it is a good idea to tailor sexual and reproductive health services to the needs of adolescents. They admitted that very limited sexual and reproductive health programs targeting adolescent needs were available in the study area. Service providers also reported very low levels of health facilities use by adolescents for sexual and reproductive health information and services. Health professionals attributed the poor sexual and reproductive health services utilization by adolescents to stigma from the society and attitudes of service providers. Conclusion. There are no targeted sexual and reproductive health programmes and services for adolescents. Services providers indicated that it is important to tailor sexual and reproductive health services to the needs of adolescents to prevent stigma, unwanted pregnancy, abortion, and sexually transmitted infections.